TAXUS BACCATA L., IN THE NATURE AND CULTURE OF EASTERN GEORGIA - Nadiradze , Tamar (EurasianUnionScientists, 2020)
The article discusses contemporary bio-ecological condition of Taxus baccata L., as one of the endangered species, in its natural spreading area in Georgia, particularly, in Batsara National Reserve and in ornamental horticulture of eastern Georgia. We have studied the periods of bud opening, vegetation ending, starting and ending of cambium action, sprout woodening process, time and rate of growth in height, and regularities of accumulation-transformation of storage carbohydrates. The studies revealed that the Yew growth duration is affected by the snowless winter and frequent droughts increased in the last decades, as they cause the lack of water in soils and badly affect the plant growth. The study of sprout woodening, cambium action peculiarities and regularities of accumulation-transformation of storage carbohydrates, prove its strong ability of frost-resistance. The study of bio-ecological peculiarities of Taxus baccata L. and its wide introduction in ornamental horticulture, greened areas and forest cultures will be useful for conservation of this endangered species.